Lack of association between PKLR rs3020781 and NOS1AP rs7538490 and type 2 diabetes, overweight, obesity and related metabolic phenotypes in a Danish large-scale study: case-control studies and analyses of quantitative traits - Almind Katrine; Lauritzen Torsten; Sandbæk Annelli; Borch-Johnsen Knut; Mogensen Mette; Andreasen Camilla; Hansen Lars; Jørgensen Torben; Pedersen Oluf; Hansen Torben (BMC, 2008)
Abstract Background Several studies in multiple ethnicities have reported linkage to type 2 diabetes on chromosome 1q21-25. Both PKLR encoding the liver pyruvate kinase and NOS1AP encoding the nitric oxide synthase 1 (neuronal) adaptor protein (CAPON) are positioned within this chromosomal region and are thus positional candidates for the observed linkage peak. The C-allele of PKLR rs3020781 and the T-allele of NOS1AP rs7538490 are reported to strongly associate with type 2 diabetes in various European-descent populations comprising a total of 2,198 individuals with a combined odds ratio (OR) of 1.33 [1.16-1.54] and 1.53 [1.28-1.81], respectively. Our aim was to validate these findings by investigating the impact of the two variants on type 2 diabetes and related quantitative metabolic phenotypes in a large study sample of Danes. Further, we intended to expand the analyses by examining the effect of the variants in relation to overweight and obesity. Methods PKLR rs3020781 and NOS1AP rs7538490 were genotyped, using TaqMan allelic discrimination, in a combined study sample comprising a total of 16,801 and 16,913 individuals, respectively. The participants were ascertained from four different study groups; the population-based Inter99 cohort (nPKLR = 5,962, nNOS1AP = 6,008), a type 2 diabetic patient group (nPKLR = 1,873, nNOS1AP = 1,874) from Steno Diabetes Center, a population-based study sample (nPKLR = 599, nNOS1AP = 596) from Steno Diabetes Center and the ADDITION Denmark screening study cohort (nPKLR = 8,367, nNOS1AP = 8,435). Results In case-control studies we evaluated the potential association between rs3020781 and rs7538490 and type 2 diabetes and obesity. No significant associations were observed for type 2 diabetes (rs3020781: pAF = 0.49, OR = 1.02 [0.96-1.10]; rs7538490: pAF = 0.84, OR = 0.99 [0.93-1.06]). Neither did we show association with overweight or obesity. Additionally, the PKLR and the NOS1AP genotypes were demonstrated not to have a major influence on diabetes-related quantitative metabolic phenotypes. Conclusion We failed to provide evidence of an association between PKLR rs3020781 and NOS1AP rs7538490 and type 2 diabetes, overweight, obesity or related quantitative metabolic phenotypes in large-scale studies of Danes.